Określenia Anny i Joachima w "Homilii na narodzenie Najświętszej Maryi Panny" Jana z Damaszku - Zięba, Łucja (Vox Patrum, 2007)
The article treats of terms concerning the parents of the Virgin Mary, that were used by John of Damask in his homily on the Nativity of the Blessed Virgin Mary. Anna and Joakeim are here described with terms referring to religiousness, fertility and obtaining the fruits of the earth. The most expressions concern Anna and her maternity, whereas Joakeim is mentioned only when Annas name appears.